Insuring the African future - Barry, Hanna (Centre for Film and Media Studies, 2015)
The African growth story has investors from around the world eyeing opportunities offered up by the continent in the form of new markets, enhanced growth potential and impressive returns. Despite the overwhelmingly positive thrust of this message, it finds itself situated against a backdrop of serious challenges, not only in Africa, but also globally, in the face of increasing financial, political and natural-catastrophe risk. In this world of tremendous risk and tremendous opportunity, the insurance industry can provide post-disaster financing, financial security, institutional investment and innovative risk management strategies to reduce levels of risk on the ground. Launched earlier this year, the Principles for Sustainable Insurance are a framework for embedding environmental, social and governance factors into insurance business and so promoting sustainable development. This creative research project argues that a robust insurance industry promotes economic growth and that the parallel developments, in the story of African growth and the risk management practices of the insurance industry, present a compelling framework for nurtured and sustainable development in Africa.